Inventory Management in Non-Food Convenience Store - Harun, Hanif Rahman; Mulyono, Nur Budi (Journal of Business and Management, 2016)
Abstract. Retail is one of the promising business sectors to run in Indonesia. Nowadays, small size retail stores such as minimarkets is counted as largely growing business in Indonesia. Along with its rapid growth, retail businesses face many problems. One of the most complicated problems in this business sector is overstocking and under stocking of inventory that may happen at the same period. PT. Idola Jaya Semesta, a growing non-food convenience store, faces this inventory problem. This research aims to get the best inventory policy for PT. Idola Jaya Semesta. The sample data to be analyzed is limited to the best-selling category which is stationary, and focused on the top ten most overstocked items by percentage in a random retail store, which is the retail store in Bintaro. The data of the inventory report in the central store and distribution center is employed as a basis data of the research. The researchers used probabilistic method and economic order quantity model to analyze the inventory practices and to propose a solution. The result of this research is an inventory policy (maximum inventory level and reorder point) that avoid those problems and maximize profit. The research founds that using EOQ results in the lowest total inventory cost for the company, it is around IDR 4 million rupiahs cheaper than the current policy in a course of a year. However the current existing â€œTSMâ€ policy of the company results in the lowest under stocking cost by IDR 68,308, not a very significant amount. In the long term the EOQ policy results in better to be used as it rises, the profitability ratio in the next 5 years using Monte Carlo Simulation for the items that have a yearly demand of over 100, but with the TSM policy it is better to use with items that have a yearly demand below 100. Ultimately, the best solution is to use the EOQ policy because it has the lowest total inventory cost and the profitability ratio of items with a yearly demand below 100 is not very significant for the companyâ€™s total profit. By using the sensitivity analysis, it is also more reliable to use the EOQ policy, when compared to the current existing TSM policy, as it is less sensitive to a change in demand compared to the current policy. The implementation plan for the company is very simple, the company employed a software engineer to create the software used to determine how much to order and the point of reorder, the companyâ€™s software engineer needs to simply change the formula of the current policy to the EOQ policy within the software program codes. Since the software is a form of digital media, it can be applied fast and at a low cost.Keywords: Inventory Management; Economic Order Quantity; Re-order Point; Non-Food; Convenience Store;Retail